Frozen - Buck, Chris; Lee, Jennifer (Screenwriter); Morris, Shane; Del Vecho, Peter; Lasseter, John; Bell, Kristen, 1980-; Menzel, Idina; Groff, Jonathan; Gad, Josh, 1981-; Fontana, Santino; Tudyk, Alan; Hinds, Ciaran, 1953-; et al. (Burbank, CA Disney, 2014)
"Fearless optimist Anna sets off on an epic journey--teaming up with rugged mountain man Kristoff and his loyal reindeer Sven--to find her sister Elsa, whose icy powers have trapped the kingdom of Arendelle in eternal winter. Encountering Everest-like conditions, mystical trolls and a hilarious snowman named Olaf, Anna and Kristoff battle the elements in a race to save the kingdom"--Container.
Videodisc release of the 2013 motion picture.
Story inspired by "The Snow Queen" by Hans Christian Andersen.
Widescreen 2.24:1.
Bonus features: Original theatrical short: "Get a horse!" (Mickey Mouse short); Music videos: "Let it go (end credit version)" music videos: Demi Lovato (English), Martina Stoessel (Spanish), Martina Stoessel (Italian), Marsha Milan (Malaysian); Original teaser trailer.
Original songs, Kristen Anderson-Lopez and Robert Lopez ; original score, Christophe Beck ; editor, Jeff Draheim ; art director, Michael Giaimo ; production designer, David Womersley ; director of cinematography, layout, Scott Beattie ; director of cinematography, lighting, Mohit Kallianpur.
Voices: Kristen Bell, Idina Menzel, Jonathan Groff, Josh Gad, Santino Fontana, Alan Tudyk, Ciaran Hinds, Chris Williams, Stephen John Anderson, Maia Wilson, Edie McClurg, Robert Pine, Maurice LaMarche, Livvy Stubenrauch, Eva Bella, Spencer Ganus, Jesse Corti, Jeffrey Marcus, Tucker Gilmore.
Keywords: Sisters -- Juvenile films; Winter -- Juvenile films; Quests (Expeditions) -- Juvenile films; Magic -- Juvenile films; Princesses -- Juvenile films; Missing persons -- Juvenile films; Snow -- Juvenile films; Magic -- Drama; Winter -- Drama; French language materials; Spanish language materials; Animation; Feature films -- United States; Animated films -- United States; Fantasy films; Children's films; Fiction films; Juvenile works; Film adaptations; Video recordings for people with visual disabilities; Video recordings for the hearing impaired